John Calvin on the Christian's Social Responsibility: Cultural Activist or "Modest Social Reformer"?. Issue 4 (4th December 2017) - Vorster, Nico
Abstract: Recently there have been heated discussions between Reformed theologians who embrace the two‐kingdoms doctrine and proponents of the Neo‐Calvinist tradition on whether Calvin held social transformationist views. This article examines the debate and argues that Calvin did not interpret the kingdom as a progressive social‐transforming reality that gradually establishes God's future eschatological reign on earth. Instead, he regarded Christ's present reign as a "backward"‐reaching reality that restores God's original created order. At the same time Calvin did not make a sharp categorical distinction between the spiritual and civil realms but depicted the civil and spiritual order as two regiments of God's one reign that mutually aid and assist each other.